2022
DOI: 10.3390/biology11010104
|View full text |Cite
|
Sign up to set email alerts
|

Psychological, Physical, and Heat Stress Indicators Prior to and after a 15-Minute Structural Firefighting Task

Abstract: Firefighters work in strenuous conditions for prolonged periods wearing up to 20 kg of personal protective equipment. This often contributes to significant heat and cardiovascular strain. This study examined the relationships between psychological and physical measures taken prior to undertaking a 15 min firefighting task, and the occurrence of heat stress and high levels of fatigue following the task. Nine qualified firefighters completed a 15 min “live burn” scenario designed to mimic a fire started by a two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…This review summarized seven research studies that measured cognitive functioning before and after firefighters completed a training exercise in high temperatures. Two studies showed improvements ( Greenlee et al, 2014 ; Walker et al, 2015 ), three showed impairments ( Hemmatjo et al, 2017 ; Zare et al, 2018 ; Hemmatjo et al, 2020 ), and two showed no effect of heat ( Abrard et al, 2021 ; Canetti et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This review summarized seven research studies that measured cognitive functioning before and after firefighters completed a training exercise in high temperatures. Two studies showed improvements ( Greenlee et al, 2014 ; Walker et al, 2015 ), three showed impairments ( Hemmatjo et al, 2017 ; Zare et al, 2018 ; Hemmatjo et al, 2020 ), and two showed no effect of heat ( Abrard et al, 2021 ; Canetti et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Using a cognitive test from the Mini Mental State examination (Folstein et al, 1975) requiring participants to count backwards from 100 by 6, 7, or 8 they found no difference in performance pre-and post-exercise. Canetti et al (2022) also measured cognition before and after a live container fire exercise (temperatures exceeded 400°C) and found no differences. They assessed cognition with three tests; a digit cancelation task in which participants had 90-s to cross out targets on a sheet of paper, a logical reasoning task in which they had 30-s to answer true or false to statements about letter pairings (see Baddeley, 1968), and a recall task in which they were presented with items for 30-s and had to recall as many as possible.…”
Section: Extreme Heat Has No Impact On Cognitionmentioning
confidence: 98%
“…In the course of their work, firefighters are exposed to several negative environmental factors, including heat exhaustion and toxic hazards, which can result in negative effects on neuro-cognitive function ( 35 ). Canetti et al investigated the effect of a simulated 15-min firefighting task on psychological and heat stress indicators in firefighters ( 36 ). The author confirmed that cognitive function was impaired due to exposure to elevated heat stress and core temperature during simulated firefighter duties.…”
Section: Discussionmentioning
confidence: 99%
“…20,21 Additionally, elevated core temperature and heat stress could cause greater fatigue and lower cognitive function in some firefighters. 22 Mitigating physiological and thermoregulatory strain is critical to prevent overexertion and musculoskeletal injury which represent the leading cause of lost-time duty in firefighters 20,21…”
Section: Role Of Environmental Heat Exposure and Strenuous Work In Fi...mentioning
confidence: 99%
“…Combining the effects of exercise and heat impairs firefighter‐specific functional balance and increases the likelihood of slips, trips, and falls, which lead to musculoskeletal injuries 20,21 . Additionally, elevated core temperature and heat stress could cause greater fatigue and lower cognitive function in some firefighters 22 . Mitigating physiological and thermoregulatory strain is critical to prevent overexertion and musculoskeletal injury which represent the leading cause of lost‐time duty in firefighters 20,21 …”
Section: Role Of Environmental Heat Exposure and Strenuous Work In Fi...mentioning
confidence: 99%